Perception of educational investment and its impact on dropout from the fiscal high school - Intriago Cusme, Nancy Evelina; Félix López, Miryam Elizabeth; Ramos Quistial, Sandra Del Carmen; Merchán Ponce, Narda Paola (SATHIRI, 2024)
This article analyzes the relationship between educational investment and dropout in Ecuador’s fiscal high school, with a focus on the province of Manabí. School dropout is a persistent challenge in Ecuador, and this case study seeks to understand how educational investment affects student retention. The methodology was based on differentiated surveys of principals and teachers for the different perspectives that contribute to more objective results. The results show a significant correlation between educational investment and attrition, supporting the idea that educational investment has a positive impact on student retention. Other factors, such as socioeconomic conditions and lack of family support, were identified as contributing to dropout. However, educational investment helps mitigate these problems by raising the quality of education and providing additional opportunities for students. This study recognizes that dropout is a complex phenomenon, influenced by multiple factors. It highlights the importance of teacher professional development and emphasizes the need for future research that combines quantitative and qualitative data for a deeper understanding of this relationship. Rectors and teachers reach a consensus on the relationship between investment and attrition, albeit with mixed opinions. This analysis highlights the importance of allocating adequate resources to education to ensure quality and accessible education in the province of Manabí. These findings have significant implications for improving education and reducing dropout in this specific region of Ecuador.